Hurricanes have eyes but can't see : and other amazing facts about wild weather - Berger, Melvin; Berger, Gilda (New York : Scholastic, 2004)
Weather can be wild. Thunderstorms, hurricanes, tornadoes, and other storms can cause accidents, damage property, and injure people. Learn about what makes wild weather and what you can do to keep safe.
Introduction -- Thunderstorms -- Monsoons -- Hurricanes -- Tornadoes -- Blizzards -- Rainstorms -- Ice storms -- Droughts -- Dust storms -- Hailstorms -- Fog -- Heat waves -- Forecasting wild weather.
Accelerated Reader AR
Keywords: Storms -- Juvenile literature; Tornadoes -- Juvenile literature; Hurricanes -- Juvenile literature; Children's questions and answers; Blizzards -- Juvenile literature; Weather -- Juvenile literature; Meteorology -- Juvenile literature